1998
DOI: 10.1046/j.1365-2044.1998.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin: touchstone or totem?

Abstract: SummaryA decrease in serum albumin concentrations is an almost inevitable finding in disease states, and is primarily mediated in the acute phase by alterations in vascular permeability and redistribution. This change is not disease specific but marked changes that persist are generally associated with a poorer prognosis. Critical appraisal of long-standing practices and the availability of alternative colloid solutions have led to a reduction in albumin replacement therapy, and a widespread tolerance of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
227
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(247 citation statements)
references
References 93 publications
5
227
0
5
Order By: Relevance
“…34 It is well documented that serum albumin levels are affected and decreased in various disease conditions, such as hepatic disorders, renal diseases, and burns. 36 The data presented in Table 1 clearly demonstrate significantly decreased serum albumin levels as the disease progressed, which occurs because FAP patients suffer from malnutrition and/or renal disorders as a result of amyloid deposition in the gastrointestinal tract and kidney. [36][37][38] In addition, Biacore analysis showed that albumin had a binding affinity for TTR and exhibited a higher affinity for TTR amyloid (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 98%
“…34 It is well documented that serum albumin levels are affected and decreased in various disease conditions, such as hepatic disorders, renal diseases, and burns. 36 The data presented in Table 1 clearly demonstrate significantly decreased serum albumin levels as the disease progressed, which occurs because FAP patients suffer from malnutrition and/or renal disorders as a result of amyloid deposition in the gastrointestinal tract and kidney. [36][37][38] In addition, Biacore analysis showed that albumin had a binding affinity for TTR and exhibited a higher affinity for TTR amyloid (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 98%
“…Normal serum albumin level ranges between 3.5 and 5.0 g/dL in adults. Hypoalbuminemia is defined as serum albumin <3.5 g/dL (Fearon et al, 1998;Margarson and Soni, 1998;Simons et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, serum albumin level may decrease due to inflammation in advanced cancer, cancer cachexia, malnutrition, chemotherapy-related malnutrition, prior surgery-related malnutrition, and terminal stage of the disease. Previous studies showed that hypoalbuminemia was an independent prognostic factor for gastrointestinal and lung cancers (Dewys et al, 1980;Margarson and Soni, 1998;O'Gorman et al, 1998;von Meyenfeldt, 2005). DOI:http://dx.doi.org/10.7314/APJCP.2015.16.14…”
Section: Discussionmentioning
confidence: 99%
“…This drop may reach levels of 1-1.15 mg/dL within 3 to 7 days. (11) Intravenous albumin administration is thought to have multiple effects (Figure 1). It is likely to regulate vascular properties by maintaining osmotic pressure and microvascular integrity; transport hormones (cortisol and thyroxine), fatty acids, biliary salts, bilirubins, and ions (calcium and magnesium); modulate acidbase balance; and exert antioxidant and anti-apoptotic effects.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…It is likely to regulate vascular properties by maintaining osmotic pressure and microvascular integrity; transport hormones (cortisol and thyroxine), fatty acids, biliary salts, bilirubins, and ions (calcium and magnesium); modulate acidbase balance; and exert antioxidant and anti-apoptotic effects. (1,(10)(11)(12) The chemical structure of serum albumin includes a thiol group that contains a sulfhydryl radical (-SH) with antioxidant properties. (13) It is responsible for 80% of thiol radicals in the circulating blood.…”
Section: In Vitro Effectsmentioning
confidence: 99%